Polyphenols from Erythrina crista-galli: structures, molecular docking and phytoestrogenic activity - Ashmawy, Naglaa S.; Ashour, Mohamed L.; Wink, Michael; El-Shazly, Mohamed; Swilam, Noha (Molecules, 2016)
Objectives: The current study aimed at exploring the secondary metabolites content of Erythrina crista-galli aqueous methanol extract and assessing its phytoestrogenic and cytoprotective activities. Methods: Isolation of the compounds was carried out using conventional chromatographic techniques. The structures of the isolated compounds were elucidated based on the UV, NMR spectral data along with their mass-spectrometric analyses. The phytoestrogenic activity was evaluated in-silico and in vitro using the Arabidopsis thaliana pER8: GUS reporter assay and the proliferation-enhancing activity of MCF-7 cells. Key findings: Phytochemical investigation of E. crista-galli aqueous methanol extract resulted in the isolation and identification of five flavonoids. The plant extract and its fractions showed significant estrogenic activities compared to controls. Conclusion: Five flavonoids were identified from E. crista-galli aqueous methanol extract. To the best of our knowledge, among these flavonoids, apigenin-7-O-rhamnosyl-6-C-glucoside was isolated for the first time from nature. Moreover, luteolin-6-C-glucoside was isolated for the first time from this plant. The plant revealed promising phytoestrogenic activities. This gives rationale to some of its pharmacological properties and suggests additional phytoestrogenic effects, which have not been reported yet.
Gesehen am 03.01.2017